2015
DOI: 10.1093/database/bau129
|View full text |Cite
|
Sign up to set email alerts
|

OntoMate: a text-mining tool aiding curation at the Rat Genome Database

Abstract: The Rat Genome Database (RGD) is the premier repository of rat genomic, genetic and physiologic data. Converting data from free text in the scientific literature to a structured format is one of the main tasks of all model organism databases. RGD spends considerable effort manually curating gene, Quantitative Trait Locus (QTL) and strain information. The rapidly growing volume of biomedical literature and the active research in the biological natural language processing (bioNLP) community have given RGD the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…First, PubMed abstracts are searched using the text mining software tool OntoMate ( 11 ) which has been integrated into the curation software ( 2 ). The search retrieves and ranks abstracts containing selected disease terms and the name and synonyms of selected genes ( Figure 1 ).…”
Section: Manual Disease Curation At Rgdmentioning
confidence: 99%
“…First, PubMed abstracts are searched using the text mining software tool OntoMate ( 11 ) which has been integrated into the curation software ( 2 ). The search retrieves and ranks abstracts containing selected disease terms and the name and synonyms of selected genes ( Figure 1 ).…”
Section: Manual Disease Curation At Rgdmentioning
confidence: 99%
“…The focus in such studies is often to design a Graphic User Interfaces and to simplify the curation work by highlighting specifi c concepts in a dedicated tool [ 16 ]. While most of these systems seem exploratory studies, some seem deeply integrated in the curation workfl ow, as shown by the OntoMate tool designed by the Rat Genome Database [ 17 ], the STRING DB for protein-protein interactions or the BioEditor of neXtProt [ 18 ]. From an evaluation perspective, the idea is to detect the beginning and the end of an entity and to assign a semantic type to this string.…”
Section: Check Of Recordsmentioning
confidence: 99%
“…OntoMate, for example, uses natural language processing to curate gene and phenotype ontology from the titles and abstracts of PubMed literature (LIU et al 2015). PubMatrix uses text mining to build a frequency matrix of term co-occurrence (BECKER et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many literature mining tools, often called “PubMed derivatives,” have been developed to facilitate the search of literature to address specific needs. OntoMate, for example, uses natural language processing to curate gene and phenotype ontology from the titles and abstracts of PubMed literature ( Liu et al 2015 ). PubMatrix uses text mining to build a frequency matrix of term co-occurrence ( Becker et al 2003 ).…”
mentioning
confidence: 99%